Calculation of Co-Cu Phase Diagrams Using The Cluster Site Approximation - Bourki, S.; Zereg, M. (Asian Journal of Chemistry, 2010)
Calculations using the cluster-site approximation have been applied to fcc phases in the Co-Cu system, where the pair exchange energies are determined by fitting to the critical temperature. The topology of the calculated coherent phase diagram is similar to the one obtained using the cluster variation method. By using different values of the adjustable parameter g, we have been able to obtain an improved phenomenological description of this system. It is suggested that the modified cluster site approximation should replace the use of large clusters in the cluster variation method for first principles phase diagram calculations for binary systems.